Population biology and behavioural aspects of the squid Doryteuthis plei (Blainville, 1823) in the northern coast of São Paulo, with emphasis on reproduction and feeding - Postuma, Felippe Aldert (2015)
This PhD thesis addresses several aspects of the biology and ecology of the squid Doryteuthis plei in the coast of São Paulo, SE Brazil, at both the population and individual levels. On the population structure of the exploited stock, it includes the patterns of reproductive activity, size-at-maturity, and biometrics of reproductive organs associated with squid size, as well as feeding habits and ontogenetic, sexual, and spatial-temporal shifts. Generalized Additive Models for Location, Scale, and Shape (GAMLSS) were used to identify such population patterns and spatial and temporal factors based on the particular small-scale fishery that targets the species around the São Sebastião Island. At the individual level, the study focused on behavioural traits in two periods of the life-cycle: (1) the reproductive phase, where the body patterns were described, generating a comprehensive ethogram for the species, and (2) the paralarval phase, where the development of swimming and predatory behaviours was detailed. Size-at-maturity was found to be 151-175 mm of mantle length (ML) for females, and 187-190 mm ML for males, that also showed the co-occurrence of two distinct maturation groups (Chapter 1). A significant peak of females gonad weight occurs in February and March especially in the island\'s South and Southeastern areas, and of males in March. An ethogram analysis showed 19 chromatic, 5 locomotor, and 12 postural components and behavioural sequences for the species, including agonistic, courtship, and mating behaviour (Chapter 2). Light chromatic components (clear and iridophore splotches) showed a longer duration than dark chromatic components, especially those associated with calm behaviour, more frequent in females. Males appeared more dedicated to disputes over resources and used fast miscellaneous visual signalling. In respect to feeding habits (Chapter 3), prey composition differed among sexes, size, maturity, and spatio-temporal pattern. Females do not stop feeding during sexual maturation and the amount of food increases with size. Cephalopods were significant preys for mature females, as well as fish and crustaceans to the largest females, while pelagic polychaetes were dominant prey for largest males. Observations and filming of D. plei paralarvae (Chapter 4) show a complex predatory behaviour on live preys, with different hunting types differing in speed and position. Aggressive intra-specific behaviour was found in the absence of prey when paralarvae show both a pursuit strategy and a rapid backward escape after attack. These findings contribute to better understand the population biology and behavior of the species and also in the future definition and guidance of fisheries management plans.